Forecasting Demand and Controlling Raw Fabric Inventory to Prevent Overstock at PT XYZ - Dardanella, Derry; Maulida, Insyirah Nurul Syifa; Irawan, Suhendi (prodima@fe.uika-bogor.ac.id, 2025)
PT XYZ is a company engaged in the textile and garment sector. The problem that occurs is the accumulation of fabric raw materials in the warehouse due to excess inventory compared to the demand received. The purpose of this research is to determine the safety stock to prevent overstock. The research method consists of forecasting along with the parameters MAD, MSE, and MAPE as validation using POM QM software. In addition, production control is carried out using the min-max method to determine the amount of inventory required. The results of the study show that the company can use the exponential smoothing forecasting method with an alpha accuracy level of 0.7, which shows that the forecast for the next period is 6,315,349 yards with a MAD value of 1,278,671 and a MAPE value of 21.76%. Furthermore, the company can reorder (ROP) 2,721,298 yards, safety stock of 1,360,649 yards with a minimum inventory of 7,802,654 yards and a maximum inventory of 15,605,307 yards.